Green synthesis of CuO nanoparticles using Lantana camara flower extract and their potential catalytic activity towards the aza-Michael reaction. Issue 24 (7th April 2020) - Chowdhury, Rakesh; Khan, Aslam; Rashid, Md. Harunar
Abstract : An easy and convenient synthesis process is reported for the synthesis of CuO nanoparticles using plant extract for use as a catalyst in the aza-Michael addition reaction. Abstract : Aza-Michael addition is one of the most exploited reactions in organic chemistry. It is regarded as one of the most popular and efficient methods for the creation of the carbon–nitrogen bond, which is a key feature of many bioactive molecules. Herein, we report the synthesis of CuO nanoparticles by an alkaline hydrolysis process in the presence of the flower extract of Lantana camara, an invasive weed, followed by calcination in air at 400 °C. Microscopic results indicated that the plant extract played an important role in the modulation of the size and shape of the product. In the presence of extract, porous CuO nanostructures are formed. While mostly aggregated rod-shaped CuO nanostructures are formed in the absence of extract. The products are pure and highly crystalline possessing the monoclinic phase. The CuO nanoparticles have been used as a catalyst in the aza-Michael addition reaction in aqueous medium under ultrasound vibration. The product yield is excellent and the catalyst is reusable up to the fifth cycle. The catalyst system can be extended to various substituted substrates with excellent to moderate yields.